Administration of a Muslim's estate under section 17 of the public trust corporation act 1995 with special reference to transfer of vehicles - Drs Nasrul, Muhammad Amrullah; Mohd Salim, Wan Noraini (IIUM Press, 2017)
As one of the administrative bodies, Amanah Raya Berhad (ARB) possesses jurisdiction in administering the deceased’s movable estate through the issuance of letters of declaration and direction respectively. Applying for such document requires the applicant to attach the fara’id certificate as part of the application. The problem, however, is the superfluity of the fara’id certificate in estate cases involving the transfer of ownership of the deceased’s vehicle. This is due to the rule set by the Road Transport Department (RTD) which allows for only a single name to be registered as the new owner, and thus renders the fara’id certificate inoperable. Since the ARB still requires the fara’id certificate in cases involving the administration of vehicles, this requirement is burdensome to the beneficiaries as they have to incur additional costs, as well as spend time and effort to obtain the certificate. This article addresses the problem in relation to estate administration by ARB involving vehicles under Section 17 of the Public Trust Corporation Act 1995 and analyses the implication of such rule towards estate administration. It is based primarily on the analysis of written sources, namely, textbooks, statutes, by laws and journals. The findings from this article show that there is a need to improve the policy of the ARB and the RTD in providing a more efficient means to the public in the administration of the estate of a Muslims.